Relationship to Erosion of Primary and Permanent Teeth of Gastroesophageal Reflux in Children: A Literature Review - Sari, M.E.; Koyutürk, A.E. (Cumhuriyet University Faculty of Dentistry cumhuriyetdentj@hotmail.com, 2010)
Gastroesophageal reflux besides being the most common illnesses in esophagus is also prevalent among children. Although it has not been fully understood the mechanism it has been shown to be related to genetic, environmental, anatomical, hormonal and neurogenic events. In the patients with Gastroesophageal reflux nutritional problems in the long run, esophageal inflammation, anemia, apnea, and aspiration pnomonia and may face problems such as narrowing of the esophagus can be observed. The relationship with dental erosion of teeth and gastric acid regurgitation or vomiting cases was shown in many studies. Especially in young children have not developed mechanisms to control reflux, Gastroesophageal reflux become more apparent with erosion in primary teeth. Gastroesophageal reflux can be detected by early dental examination; progression of the disease can be prevented with early diagnosis. The dental erosion in pediatric patient having Gastroesophageal reflux may become preventable with the protection measures and the conscious of patients.
Çocuklarda Gastroözefageal Reflünün Süt ve Daimi Diş Erozyonu ile İlişkisi: Literatür Derlemesi